On the taxonomy and distribution of Varanus salvator andamanensis Deraniyagala, 1944 (Reptilia: Varanidae), including a redescription of the type specimens and a discussion about its allopatric co-occurrence with V. s. macromaculatus on the Nicobar Islands - Samarasinghe, Dinal J. S.; Koch, André; Harikrishnan, Surendran; Manamendra-Arachchi, Kelum; Chandi, Manish (Zootaxa, 2020)
We provide a detailed redescription of the two original type specimens of the little-known, endemic Andaman water monitor, Varanus salvator andamanensis Deraniyagala, 1944. Examination of further voucher specimens allows for an expanded morphological diagnosis of this island taxon and comparison with other currently recognized subspecies of the wide-spread Southeast Asian water monitor. Based on the specimens examined, V. s andamanensis is characterized by a homogenous black dorsal background colour, with five to seven, more or less distinctive transverse rows of small spots or ocelli, light yellowish dots arranged sporadically between transverse spot/ocelli rows on the body, light yellowish coloured spots distributed sporadically throughout both forelimbs and hind limbs; 17–18 prominent rows of light spots continuing from base of tail to its tip dorsally with sporadically arranged dots on lateral sides of tail; and higher scale counts in transverse dorsal scale rows. Based on photographic evidence and examination of museum specimens, V. s. andamanensis inhabits both the Andaman and southern Nicobar Islands, which politically belong to the Republic of India. In addition, we confirm the presence of V. s. macromaculatus in the northern and central Nicobar Islands, thus providing evidence for the allopatric co-occurrence of two different water monitor subspecies in these remote archipelagos.